Evaluation of RAPD markers for taxonomic relationships in some aquatic species of Utricularia L. (Lentibulariaceae) - Rahman, Mohammad Oliur (Bangladesh Journal of Plant Taxonomy, 2006)
Random amplified polymorphic DNA (RAPD) markers were used to assess relationship across nine aquatic species of Utricularia. The highest numbers of RAPD bands were detected in Utricularia bremii and U. intermedia. The highest genetic similarity was observed between U. australis and U. dimorphantha; between U. australis and U. vulgaris; and between U. dimorphantha and U. macrorhiza indicating that these species are closely related. Unweighted pair group method with arithmetic mean (UPGMA) analysis based on the RAPD profile in aquatic Utricularia resolved the taxa into three clusters: the first cluster included U. aurea, U. australis, U. dimorphantha, U. macrorhiza and U. vulgaris; the second cluster constituted from U. bremii and U. gibba while U. intermedia formed the third cluster with U. minor. The Neighbour Joining (NJ) tree showed that aquatic species could be placed in two main groups and the results obtained from the NJ analysis were coherent with that of the UPGMA clustering method. The molecular findings revealed from this study support the systematic relationships in Utricularia inferred from morphological investigations. Key words: Aquatic Utricularia, Genetic affinity, Neighbour Joining, RAPD, Systematic relationships, UPGMA DOI: 10.3329/bjpt.v13i2.580 Bangladesh J. Plant Taxon. 13(2): 73-82, 2006 (December)